Perbandingan Strategi Pemasaran Online Dan Offline di Era Pandemi Covid-19 - Popon Sri Susilawati; Farhan Hilal; Nahla Aulia Azzahra; Shafa Luthfiah Nurlaeli (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research is motivated by the growing development of information technology systems which have an impact on the development of marketing, namely utilizing information technology in making online purchasing transactions. Purchasing online is one of the alternatives chosen in this era of the COVID-19 pandemic for reasons of convenience, speed and practicality. In addition, not a few consumers also choose to purchase offline for reasons of trust and security. There is convenience in purchasing online but the goods ordered do not match the picture. While offline purchases of the desired goods can be known specifications, but the range of locations and costs are obstacles for consumers. For this reason, the author is interested in examining the comparison of online and offline marketing strategies in the era of the COVID-19 pandemic. The purpose of this study is to determine whether there are differences in the comparison of marketing strategies with online and offline systems. The method used in this paper is a qualitative method. The results of this method are narrative data and not numbers. In the current era of the Covid-19 pandemic, people prefer to shop online rather than offline, so there is a great opportunity to use social media technology as a means of selling. Keywords: Marketing Strategy, Online and Offline